Green Synthesis of Molecules for the Treatment of Neglected Diseases - Anghinoni, João M.; Dilelio, Marina C.; Shiguemoto, Cristiane Y.K.; Schumacher, Ricardo F.; Baroni, Adriano C.M.; Lenardão, Eder João (Current Topics in Medicinal Chemistry, 2023)
Neglected tropical diseases (NTDs) affect mainly poor and marginalized populations of tropical and subtropical areas in 150 countries. Many of the chemical processes involved in the synthesis of active pharmaceutical ingredients (APIs) are highly polluting and inefficient, both in terms of materials and energy-consuming. In this review, we present the green protocols developed in the last 10 years to access new small molecules with potential applications in the treatment of leishmania, tuberculosis, malaria, and Chagas disease. The use of alternative and efficient energy sources, like microwaves and ultrasound, as well as reactions using green solvents and solvent-free protocols, are discussed in this review.
Keywords: Neglected tropical diseases